Autonomous Soft Actuators: An Autonomous Soft Actuator with Light‐Driven Self‐Sustained Wavelike Oscillation for Phototactic Self‐Locomotion and Power Generation (Adv. Funct. Mater. 15/2020). (14th April 2020) - Yang, Lulu; Chang, Longfei; Hu, Ying; Huang, Majing; Ji, Qixiao; Lu, Pin; Liu, Jiaqin; Chen, Wei; Wu, Yucheng
Abstract : In article number 1908842, Ying Hu and co‐workers construct an artificially autonomous soft robot based on a curled droplet‐shaped carbon nanotube bimorph structure, which can produce a constant white light‐driven continuous oscillating motion in a wavelike fashion. It can also autonomously and continuously crawl towards the light source in a wave‐propagating manner under constant light irradiation, exhibiting phototactic self‐locomotion.